La forme contemporaine d’existence de la monnaie dans une perspective marxiste - Nicolas Piluso (Revue de la Régulation)
The purpose of this article is to question the assertion usually made about the Marxian theory of money: the latter would only be capable of accounting for material forms of money. We show that elements of Marxian theory make it possible to account for the evolution of material monetary forms towards an immaterial form. Furthermore, Marxian theory can maintain its consistency and retain the principle of labor value as long as we consider (with Jean Cartelier) that monetary creation does not take place ex nihilo.